PENGARUH PEMBELAJARAN MENGGUNAKAN VIRTUAL LABORATORY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI GELOMBANG - Kansil, Monica J.; Warouw, Zusje W. M; Harahap, Fransiska (SOSCIED, 2024)
This study aims to determine the influence of learning using virtual laboratories on students' critical thinking skills on wave materials. The research was conducted at SMP Negeri 6 Tondano, Academic Year 2023-2024. This study uses a Quasi Experiment consisting of 2 classes, namely the Experiment class with 15 students and the control class with 16 students. The results of this study showed that there was a difference in the results of the critical thinking ability of the experimental class that was treated using virtual laboratory-assisted learning media and the control class using conventional methods. This difference can be seen from the average results of the post-test critical thinking ability of the experimental class that has been given learning using the virtual laboratory is 70.67 while the pre-test of the control class that uses conventional learning is 45.63. This is also evident from the results of the t-test calculation which produced a value of .